2022
DOI: 10.1002/da.23278
|View full text |Cite
|
Sign up to set email alerts
|

One‐year incidence, predictors, and accuracy of prediction of suicidal thoughts and behaviors from the first to second year of university

Abstract: Background Research is scarce on the prospective predictors of first onset suicidal thoughts and behaviors (STB) and the accuracy of these predictors in university students, particularly in low‐and‐middle income countries. Therefore, we assessed the 1‐year incidence of STB among first‐year students, a broad range of prospective predictors of STB incidence, and evaluated the prediction accuracy of a baseline multivariate risk prediction model to identify students at highest risk for STB onset over the subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Noteworthily, suicidal ideation at baseline could be leveraged by the machine to predict suicidal ideation after six months, but it did not yield a strictly statistically significant role. To our knowledge, there have been several studies implementing machine learning models leveraging previous suicidal ideation to predict future suicidal ideation (Benjet et al, 2022;Liao et al, 2022;Malone et al, 2021), although timeframes from baseline to follow-up did not coincide with our six-month timeframe. Substantially, previous suicidal ideation is an important is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Noteworthily, suicidal ideation at baseline could be leveraged by the machine to predict suicidal ideation after six months, but it did not yield a strictly statistically significant role. To our knowledge, there have been several studies implementing machine learning models leveraging previous suicidal ideation to predict future suicidal ideation (Benjet et al, 2022;Liao et al, 2022;Malone et al, 2021), although timeframes from baseline to follow-up did not coincide with our six-month timeframe. Substantially, previous suicidal ideation is an important is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Discussionmentioning
confidence: 93%
“…Noteworthily, suicidal ideation at baseline could be leveraged by the machine to predict suicidal ideation after six months, but it did not yield a strictly statistically significant role. To our knowledge, there have been several studies implementing machine learning models leveraging previous suicidal ideation to predict future suicidal ideation (Benjet et al, 2022; Liao et al, 2022; Malone et al, 2021), although timeframes from baseline to follow-up did not coincide with our six-month timeframe. Substantially, previous suicidal ideation is an important factor, posing a greater risk of future suicidal ideation and suicidal behavior (Bafna et al, 2022), but in our analysis did not reach canonical statistical significance (although it should be taken into account that the machine learning model would lose a great proportion of its accuracy without data from previous suicidal ideation – Figure 3A).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have been several studies implementing machine learning models leveraging previous suicidal ideation to predict future suicidal ideation (Benjet et al. , 2022 ; Liao et al. , 2022 ; Malone et al.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies on first-onset suicidal thoughts and behaviors have been conducted among college students as this group appears to be at the greatest risk of developing first-onset suicidal thoughts and behaviors. Two studies among college students found that adverse experiences such as dating violence and physical abuse before the age of 17, betrayal by someone other than the partner [ 19 ], ongoing arguments or breakup with a romantic partner, emotional abuse, parental death and lack of a reliable support system [ 20 ] were strong predictors for first-onset suicidal thoughts and behaviors.…”
Section: Introductionmentioning
confidence: 99%